2022
DOI: 10.3390/ijms23010535
|View full text |Cite
|
Sign up to set email alerts
|

Reduced RBPMS Levels Promote Cell Proliferation and Decrease Cisplatin Sensitivity in Ovarian Cancer Cells

Abstract: Worldwide, the number of cancer-related deaths continues to increase due to the ability of cancer cells to become chemotherapy-resistant and metastasize. For women with ovarian cancer, a staggering 70% will become resistant to the front-line therapy, cisplatin. Although many mechanisms of cisplatin resistance have been proposed, the key mechanisms of such resistance remain elusive. The RNA binding protein with multiple splicing (RBPMS) binds to nascent RNA transcripts and regulates splicing, transport, localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 109 publications
0
10
0
Order By: Relevance
“…RBPMS knockout has been associated with increased invasion ability in ovarian cancer [ 17 ]. We assessed the effect of RBPMSA and RBPMSC overexpression in the migration and invasiveness potential in ovarian cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…RBPMS knockout has been associated with increased invasion ability in ovarian cancer [ 17 ]. We assessed the effect of RBPMSA and RBPMSC overexpression in the migration and invasiveness potential in ovarian cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…The PCR data showed that five out of eight genes correlated well with the RNAseq data ( Supplementary Table S4 and Figure S6 ). Deregulation of most of these genes has already been associated with cancer progression, metastasis, and immune system response [ 10 , 17 , 21 , 22 , 23 ]. For example, interferon induced protein 44 (IFI44), one of the most increased transcripts upon A2780CP20-RBPMSA overexpression, has been linked to the suppression of the proliferation of human melanoma cell lines [ 24 ] as well as immune response to autoimmune disease [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations